Pertumbuhan benih ikan gabus (Channa striata) pada media pemeliharaan akuaponik menggunakan pakan komersil dengan komposisi protein berbeda - Niti, Eukharistian; Mudeng, Joppy D.; Ngangi, Edwin L. A.; Pangkey, Henneke; Monijung, Revol D.; Longdong, Sammy N.J. (Universitas Sam Ratulangi, 2024)
This research aimed to determine the growth of snakehead fries t reared in aquaponic media and fed commercial fish food. The treatments consisted of treatment A with a protein content of 40%, B with a protein content of 35%, and C with a protein content of 30%, each with three replications. The research was conducted for 32 days. The research found the absolute growth of treatment a was 1.34 g, treatment b was 0.775 g, and treatment C was 0.605 g. The daily growth rate for treatment a was 4.18%, treatment b 2.42%, and treatment C 1.89%. Linear regression analysis between protein content in food and growth weight of snakehead fish fry had a strong relationship to both absolute growth and specific growth rate. The higher the protein content, the higher the weight growth of snakehead fry. Keywords: snakehead fish, aquaponic, commercial food, protein